PENGARUH PRICE DISCOUNT DAN SHOPPING LIFESTYLE TERHADAP PEMBELIAN IMPULSIF PADA PENGGUNA SHOPEE GENERASI Z SUKABUMI - Selia; Maulana, Mochamad Afrizal (Universitas Muhammadiyah Jakarta, 2026)
The rapid growth of e-commerce has led to significant changes in consumer purchasing behavior, particularly among Generation Z, who demonstrate high levels of digital platform engagement. Shopee, as one of Indonesia’s leading e-commerce platforms, offers various promotional stimuli that may trigger impulsive buying behavior. This study aims to analyze the influence of price discounts and shopping lifestyle on impulsive buying among Generation Z Shopee users in Sukabumi City. The research employs a quantitative associative approach using a survey method. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling. Data analysis was conducted using multiple linear regression with IBM SPSS Statistics version 31. The results indicate that both price discounts and shopping lifestyle have a positive and significant effect on impulsive buying, both partially and simultaneously. These findings provide theoretical implications by reinforcing the role of price-based promotional stimuli and lifestyle-related factors in explaining impulsive buying behavior within the context of digital commerce, particularly among Generation Z consumers in developing urban areas. Keywords: E-commerce, Impulsive Buying, Price Discount, Shopee, Shopping Lifestyle.